Effect of copper and iron substitution on the structures and electrochemical properties of LiNi0.8Co0.15Al0.05O2 cathode materials. Issue 5 (5th February 2020) - Xi, Zhao; Wang, Zhixing; Peng, Wenjie; Guo, Huajun; Wang, Jiexi
Abstract: Cu and Fe are the main impurity elements in the hydrometallurgical regeneration of spent lithium‐ion batteries. Hence, it is important to study the effect of Cu and Fe doping on the structures and electrochemical properties of cathode materials. In this study, a series of Cu‐ and/or Fe‐doped LiNi0.8 Co0.15 Al0.05 O2 cathode materials are synthesized by spray pyrolysis and high‐temperature solid‐state method. The inductively coupled plasma (ICP), X‐ray diffraction (XRD), and Rietveld refinement results reveal that Cu and Fe can incorporate into the crystal lattice and cation mixing is suppressed. The X‐ray photoelectron spectroscope (XPS) results show that the relative ratio of Ni 2+ /Ni 3+ on the surface is effectively decreased. Electrochemical results display that the electrochemical performances of Cu‐ and/or Fe‐doped samples are improved when the atomic ratio of Ni to Cu and Ni to Fe is greater than 79.0 and 399.0, respectively. The dQ / dV, GITT, EIS, XRD, and XPS studies indicate that the structure stability, Li + diffusion coefficient, and charge transfer can be increased by appropriate Cu and/or Fe substitution. The results suggest that appropriate Cu and Fe can be doped into LiNi0.8 Co0.15 Al0.05 O2 as beneficial elements rather than removed as impurities. Abstract : The electrochemical performances can be improved by Cu and Fe doping. The mechanism of the effect of Cu and Fe doping on the material is studied. Spent lithium‐ion battery can be regenerated without deep separation of Cu and Fe.